Activation of calcium peroxide by nitrogen and sulfur co-doped metal-free lignin biochar for enhancing the removal of emerging organic contaminants from waste activated sludge. (April 2023) - Dong, Cheng-Di; Cheng, Jia-Wei; Chen, Chiu-Wen; Huang, Chin-Pao; Hung, Chang-Mao
Graphical abstract: Highlights: Nitrogen/sulfur lignin-based biochar (N-S-LGBC) was calcium peroxide activator. Calcium peroxide (CP) effectively degraded 4-nonylphenol over N-S-LGBC. N-S-LGBC-CP increased biodegradable organics in wastewater sludge. N-S-LGBC-CP treatment of activated sludge altered its microbial community structure. Abstract: The accumulation of emerging organic contaminants (EOCs) in waste activated sludge (WAS) is a global concern. In this study, a multi-heteroatom nitrogen and sulfur was successfully embedded into lignin-based biochar (N-S-LGBC) and used it to activate calcium peroxide (CP) for the degradation of 4-nonylphenol (4-NP) in WAS. N-S-LGBC/CP was effective in degrading 85 % of 4-NP within 12 h through the activation of CP owing to hydroxyl radicals and singlet oxygen species generated from the synergism among pyrrolic-N, thiophenic-S, and lattice oxygen, i.e., active sites responsible for 4-NP degradation. These results highlight substrate biodegradability for subsequent bioprocesses that improves WAS treatment in EOC degradation by the N-S-LGBC/CP-mediated process. There was abundance of distinct Aggregatilinea genus within the phylum Chloroflexi during N-S-LGBC/CP treatment, indicating high 4-NP pretreatment efficiency in WAS. This work provides a new understanding of N-S-co-doped carbocatalysts in green and sustainable hydroxyl radical-driven carbon advanced oxidation (HR-CAOP) platforms for WAS remediation.